A 4π time-of-flight detector for the ND280/T2K upgrade. (12th January 2022) - Korzenev, A.; Barao, F.; Bordoni, S.; Breton, D.; Cadoux, F.; Favre, Y.; Khabibullin, M.; Khotyantsev, A.; Kudenko, Y.; Lux, T.; Maalmi, J.; Mermod, P.; et al.
Abstract: ND280 is a near detector of the T2K experiment which is located in the J-PARC accelerator complex in Japan. After a decade of fruitful data-taking, ND280 is scheduled for upgrade. The time-of-flight (ToF) detector, which is described in this article, is one of three new detectors that will be installed in the basket of ND280. The ToF detector has a modular structure. Each module represents an array of 20 plastic scintillator bars which are stacked in a plane of 2.4 × 2.2 m 2 area. Six modules of similar construction will be assembled in a cube, thus providing an almost 4π enclosure for an active neutrino target and two TPCs. The light emitted by scintillator is absorbed by arrays of large-area silicon photo-multipliers (SiPMs) which are attached to both ends of every bar. The readout of SiPMs, shaping and analog sum of individual SiPM signals within the array are performed by a discrete circuit amplifier. An average time resolution of about 0.14 ns is achieved for a single bar when measured with cosmic muons. The detector will be installed in the basket of ND280, where it will be used to veto particle originating outside the neutrino target, improve the particle identification and provide a cosmic trigger for calibration of detectors which are enclosed inside it.